Application of the Numbered Heads Together (NHT) Cooperative Learning Model to Increase Learning Motivation and Learning Outcomes of Class XI IPS B Students at SMA IT Granada Samarinda - Arnianti Arnianti; Sudarman Sudarman; Noor Ellyawati (Faculty of Teacher Training and Education, Mulawarman University, 2022)
Application of Numbered Heads Together (NHT) Cooperative Learning Modelaims to improve and improve the learning process in economics class XI IPS B SMA IT Granada which is carried out collaboratively between researchers and economics teachers. The subjects of this study were students of class XI IPS B which consisted of 15 students. This research was conducted for three cycles. Data collection consisted of observation, documentation, tests and distribution of learning motivation questionnaires. Data analysis used is descriptive analysis. The results of this study indicate that the type cooperative learning modelNumbered Heads Togethercan increase learning motivation and student learning outcomesclass XI IPS B at SMA IT Granada. From the results of the research that has been done, it can be concluded that using the Numbered Heads Together cooperative learning model can improve learning outcomes and learning motivation. This is indicated by an increase in learning motivation (cycle I to cycle II by 4% and cycle II to cycle III by 6.33%) and learning outcomes (cycle I to cycle II by 33% and cycle II to cycle III by 13%) in each cycle.